Transforming Healthcare Through Information Systems Proceedings of the 24th International Conference on Information Systems Development - Vogel, Doug; Guo, Xitong; Linger, Henry; Barry, Chris; Lang, Michael; Schneider, Christoph (Lecture Notes in Information Systems and Organisation, 2016)
This book introduces ongoing reflections within the research community on established information systems development topics and emerging concepts, approaches and ideas in the field of healthcare information systems. By promoting research on theoretical and methodological issues related to both information systems development in general and healthcare information systems in particular, it presents current research in order to promote improved practice. It comprises a selection of the best papers presented at the 24th International Conference on Information Systems Development (ISD) held in Harbin, China, August 25 - 27, 2015.